PUBLIC AGENCY PERFORMANCE IN THE IMPLEMENTATION PUBLIC INFORMATION DISCLOSURE Act IN YOGYAKARTA SPECIAL REGION - Daru Nupikso (BPSDMP Kominfo Manado, 2017)
Public Information Disclosure Act (UU KIP) is valid since 2010, and public bodies throughout Indonesia are required to implement it in accordance with established provisions. In essence, UU KIP is a manifestation of human rights in obtaining information which one of its aims is to encourage public participation in the process of public policy making. The United Nations (UN) states, to achieve community participation is required three stages, and information disclosure is the initial stage and for Indonesia it is identical with the implementation of UU KIP. This research will answer how far the performance of public bodies in implementing KIP Law. With the mixed method, that is quantitative (survey and content analysis) and qualitative (interview and observation), this research uses Sekuensial Eksplanatoris strategy. The results of the study mention the performance of public bodies are categorized as being. Information on public budgets is still very low, public bodies are better vertical than other public bodies. In general, public bodies have not been able to properly implement public information disclosure due to resource and commitment factors. In addition, the emergence of regulatory disharmonization among policy makers contributed to weakening the implementation performance of UU KIP. Keywords: Openness, Freedom of Information Law, Public Agencies Undang Undang Keterbukaan Informasi Publik (UU KIP) berlaku sejak tahun 2010, dan badan publik di seluruh Indonesia wajib mengimplementasikannya sesuai dengan ketentuan yang telah dibuat. Secara hakiki, UU KIP merupakan perwujudan hak asasi manusia dalam memperoleh informasi yang salah satu tujuannya adalah mendorong partisipasi masyarakat dalam proses pengambilan kebijakan publik. Perserikatan Bangsa Bangsa (PBB) menyebutkan, untuk mewujudkan partisipasi masyarakat tersebut diperlukan tiga tahapan, dan keterbukaan informasi merupakan tahap awal dan bagi Indonesia hal ini identik dengan implementasi UU KIP. Penelitian ini akan menjawab sejauhmana kinerja badan publik dalam mengimplementasikan UU KIP. Dengan metode campuran, yaitu kuantitatif (survey dan analisis isi) dan kualitatif (wawancara dan observasi), penelitian ini menggunakan strategi Eksplanatoris Sekuensial. Hasil penelitian menyebutkan kinerja badan publik dikategorikan sedang. Informasi mengenai anggaran publik masih sangat rendah, badan publik vertikal lebih baik dibanding badan publik lainnya. Secara umum badan publik belum mampu mengimplementasikan keterbukaan informasi publik secara baik karena faktor sumber daya dan komitmen. Selain itu, munculnya disharmonisasi regulasi di antara pengambil kebijakan ikut memperlemah kinerja implementasi UU KIP. Kata kunci: Keterbukaan, UU KIP, Badan Publik